Kadar IL-10 plasma berkorelasi positif dengan kadar IgM anti PGL-1 pada narakontak serumah pasien kusta tipe multibasiler - Ida Ayu Uttari Priyadarshini; Nyoman Suryawati; Luh Made Mas Rusyati (DiscoverSys Inc., 2022)
Introduction: A healthy person who contacts people diagnosed with leprosy can be at a high risk of being infected with leprosy with a predominance of the subclinical stage. The MB type infection has a 4-10 times greater risk of developing into a clinical form. Early detection of subclinical leprosy is important so that it can play a role in the process of eliminating leprosy. If it is not screened, most of the subclinical stage leprosy can develop into the clinical stage and can cause physical deformities. Phenolic glycolipid-1 (PGL-1) is a specific antigen for M.leprae and Interleukin-10 (IL-10) is an anti-inflammatory cytokine that shows the body's immune response. Research on the relationship between levels of IL-10 and IgM anti-PGL-1, especially in Bali, has not been carried out, so this study aims to find a relationship between levels of IL-10 and levels of IgM anti-PGL-1 in household contacts of multibacillary leprosy patients. Methods: This research is an analytical observational study with a cross-sectional and was carried out in February-May 2021 at the Dermatology and Venereology Polyclinic and Clinical Pathology Laboratory, Sanglah Hospital Denpasar, and the Leprosy reference laboratory, Tropical Diseases Center, Universitas Airlangga. Samples aged 18-65 years were selected through Consecutive Sampling according to inclusion and exclusion criteria. The sample was taken from venous blood and then checked for levels of PGL-1 and IL-10. Data analysis using SPSS version 23. The results were considered significant if p<0.05. Results: The mean level of IgM anti-PGL-1 in the contact group vs. the non-contact group was 863.07 ± 789.04 u/ml vs 247.75 ± 161.60 u/ml. The mean levels of IL-10 in the contact and non-contact groups were 121.09 ± 144.11 pg/ml and 46.04 ± 11.27 pg/ml. There was a significant difference in levels of IL-10 and IgM anti-PGL-1 in the contact group and non-contact groups (p<0.05) and a weak positive relationship (r=0.296, p=0.02) between levels of IL-10 and anti-PGL-IgM. 1. Conclusion: The levels of IgM anti-PGL-1 and IL-10 in the contacts were higher than in the non-contacts with a significant difference. Pendahuluan: Narakontak merupakan salah satu kelompok dengan risiko tinggi terinfeksi kusta dengan dominansi stadium subklinis. Pada infeksi tipe MB memiliki resiko 4-10 kali lebih besar berkembang menjadi bentuk klinis. Deteksi dini pada penyakit kusta subklinis ini menjadi penting sehingga dapat berperan dalam proses eliminasi kusta. Jika dibiarkan sebagian besar kusta stadium subklinis dapat berkembang menjadi kusta klinis dan dapat menimbulkan deformitas pada fisik. Phenolic glycolipid-1 (PGL-1) merupakan antigen spesifik untuk M. leprae dan Interleukin-10 (IL-10) merupakan sitokin anti-inflamasi yang menunjukkan respon imun tubuh. Penelitian mengenai hubungan antara kadar IL-10 dan IgM anti PGL-1 khusunya di Bali belum dilakukan, sehingga penelitian ini bertujuan mencari hubungan antara kadar IL-10 dengan kadar IgM anti PGL-1 pada narakontak serumah pasien kusta tipe multibasiler. Metode: Penelitian merupakan studi observasional analitik dengan pendekatan potong lintang dan dilaksanakan bulan Februari-Mei 2021 di Poliklinik Kulit dan Kelamin dan Laboratorium Patologi Klinik, RSUP Sanglah Denpasar dan laboratorium rujukan Leprosy, Tropical Diseases Centre, Universitas Airlangga. Sampel berusia 18-65 tahun dipilih melalui Consecutive Sampling sesuai kriteria inklusi dan eksklusi. Sampel dilakukan pengambilan darah vena kemudian diperiksa kadar PGL-1 dan IL-10. Analisis data menggunakan SPSS versi 23. Hasil dianggap signifikan jika p<0,05. Hasil: Rerata kadar IgM anti PGL-1 kelompok narakontak vs bukan narakontak sebesar 863,07 ± 789,04 u/ml vs 247,75 ± 161,60 u/ml. Rerata kadar IL-10 kelompok narakontak dan bukan narakontak sebesar 121,09 ± 144,11 pg/ml dan 46,04 ± 11,27 pg/ml. Terdapat perbedaan signifikan pada kadar IL-10 dan IgM anti PGL-1 pada kelompok narakontak dan bukan narakontak (p<0.05) serta hubungan positif lemah (r=0,296, p=0,02) antara kadar IL-10 dengan IgM anti PGL-1. Simpulan: Kadar IgM anti PGL-1 dan IL-10 pada narakontak lebih tinggi dari non narakontak dengan perbedaan yang signifikan.